Surface plasmon resonance and microscale thermophoresis approaches for determining the affinity of perforin for calcium ions - Naneh, Omar; Kozorog, Mirijam; Merzel, Franci; Gilbert, Robert; Anderluh, Gregor (Frontiers in Immunology, 2023)
Perforin is a pore-forming protein that plays a crucial role in the immune system by clearing virus-infected or tumor cells. It is released from cytotoxic granules of immune cells and forms pores in targeted lipid membranes to deliver apoptosis-inducing granzymes. It is a very cytotoxic protein and is therefore adapted not to act in producing cells. Its activity is regulated by the requirement for calcium ions for optimal activity. However, the exact affinity of perforin for calcium ions has not yet been determined. We conducted a molecular dynamics simulation in the absence or presence of calcium ions that showed that binding of at least three calcium ions is required for stable perforin binding to the lipid membrane. Biophysical studies using surface plasmon resonance and microscale thermophoresis were then performed to estimate the binding affinities of native human and recombinant mouse perforin for calcium ions. Both approaches showed that mouse perforin has a several fold higher affinity for calcium ions than that of human perforin. This was attributed to a particular residue, tryptophan at position 488 in mouse perforin, which is replaced by arginine in human perforin. This represents an additional mechanism to control the activity of human perforin.